Addressing statelessness in Kenya through a confluence of litigation, transitional justice, and community activism: reflecting on the cases of the Nubian, Makonde and Shona communities (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This article outlines the challenge of statelessness in Kenya and proceeds to focus on two seminal cases filed by the Nubian community against the Kenyan state: one before the African Commission on Human and Peoples’ Rights and the other at the African Committee of Experts on the Rights and Welfare of the Child. Attention then turns to Kenya’s transitionaljustice agenda and its interaction with the plight of stateless persons in Kenya. Through the experiences of the Nubian, Makonde and Shona communities, the article also explores the role of community-led activism infurthering the cause of ending statelessness in Kenya. It concludes with key lessons to be learned from utilising litigation, transitional justice and community-led activism as part of the struggle for the rights of stateless persons in Kenya. It relies on desk-review and research of the Nubian cases, Kenya’s truth commission report and other official inquires, civil society reports, the 2010 Constitution and related laws.